An increase of the health care cost of diabetes mellitus type 2: a precise review on economic impact of diabetes - Islam, Mohd Aminul; Azad, Abul Kalam (INSI Publications, 2014)
Since the last decade chronic diseases is a major contributor for rapid rise in healthcare cost in developing countries. It is apparent from published economic studies that people with diabetes account for between 2 and 3% of the total health care budget in every country consequently, an increase in the incidence, and therefore the prevalence, of diabetes will have a considerable economic impact. It is also apparent, however, that better health economic studies are needed. Objective: The study aim was to highlight the economic burden for diabetes mellitus type2 on world economy and individual patients care cost. Results: It was estimated that around 54% of deaths in developing countries are due to chronic non- communicable diseases which is predicted to rise by 65% by 2030. Diabetes mellitus is among the most prevalent chronic diseases suffered by more than 180 million people worldwide. By 2030 it is estimated that around 400 million people in the world will be afflicted with diabetes. Annual deaths attributable to diabetes are probably as high as 3 million with more than 80% occur in developing countries. In Bangladesh, the average annual cost of care was found US $ 314 (direct cost US $ 283 and indirect cost US $ 37) ranging from US $ 23 to US $ 1334. By 2020 it is expected that the Canadian economy will lose $11 billion annually as a result of the net mortality of diabetes patients, and long-term care costs for diabetes patients are expected to jump from $1 billion to $2.7 billion annually over that time period. The average annual cost per diabetic patient of Mexican was $708 USD, the total annual cost of diabetics was 2,618,000 USD,15.46% of health spending and 0.79% of GDP. Conclusion: Furthermore, although it is relatively easy to assess the direct costs associated with the disease, better methods are needed to measure the indirect and intangible costs of diabetes to enable full assessment of the economic impact of the disease.